The child's world : triggers for learning (Camberwell, Vic. : Australian Council for Educational Research, 2000)
Perspectives on children's thinking. Experiences of place and space. Spatial - visual reasoning. Environmental experience: perceptions and judgments.
Keywords: Education; Cognition; Cognition in children -- Study and teaching; Experience in children; Reasoning in children -- Study and teaching